The influence of surface properties on sliding contact temperatureand friction for Polyetheretherketone (PEEK) - Laux,K; Jean-Fulcrand,A; SUE,HJ; BREMNER,T; Wong,JSS (Polymer, 2016)
Polyetheretherketone (PEEK) polymers are increasingly used intribological applications. An important aspect of PEEK tribology is thesurface temperature reached during sliding. However, most knowledge offrictional heating in PEEK is based on post-hoc analysis of debris andwear surfaces. In this study, infrared thermography was used to observethe full field temperature map of PEEK during ball-on-disc sliding.Although the measured temperatures were below any thermal transition, theresults matched closely to those predicted by flash temperature models.Additionally, friction studies were performed with steel and sapphirecounterfaces. It was observed that PEEK debris was readily deposited tosteel but not on sapphire. The friction studies also indicated a greateradhesive friction response for PEEK against steel compared to sapphire.The transfer of PEEK material to the steel surface may elevate thetemperature at the sliding interface. Analysis of films formed on steelsuggests that the transferred PEEK was oriented in the direction ofsliding. The deposition of debris and formation of oriented filmsresembled a high temperature drawing process, which was likely to be dueto localized frictional heating. The results of this study illustrate theimportant role transfer films play in determining both the friction andtemperature response of the PEEK wear interface.